21-Gene Recurrence Assay Associated With Favorable Metabolic Profiles in HR-Positive, HER2-Negative Early-Stage Breast Cancer Patients - Zhu, Yifei; Wang, Tiange; Tong, Yiwei; Chen, Xiaosong; Shen, Kunwei (Frontiers in Endocrinology, 2021)
Background: Comprehensive investigations of the associations between 21-gene recurrence assay and metabolic profiles in Chinese breast cancer patients are limited. Methods: We evaluated the relations of the 21-gene recurrence risk score (RS) and the expression of cancer-related genes with metabolic factors and biomarkers of insulin and the insulin-like growth factor (IGF) axis, and examined the interactions between the 21-gene RS and these metabolic profiles on breast cancer recurrence in Chinese women with HR-positive, HER2-negative early-stage breast cancer. Results: The 21-gene RS was inversely associated with body mass index (beta: -0.178 kg/m2; P=0.040), the homeostasis model assessment of insulin resistance index (beta: -0.031; P=0.042), insulin (beta: -0.036 uIU/mL; P=0.009), and C-peptide (beta: -0.021 ug/L; P=0.014), and was positively associated with high-density lipoprotein cholesterol (beta: 0.025 mmol/L; P=0.004), which were driven by the relation patterns between specific cancer-related genes and these metabolic profiles. Each 10-unit increase in the 21-gene RS was associated with 28% (95% CI: 5%-47%) higher risk of breast cancer recurrence; this association was also observed in patients with favorable metabolic profiles in relevant to an absence of obesity, insulin resistance, hyperglycemia, hypertension, or dyslipidemia (28%-44% higher risk) and among women with a low level of insulin, C-peptide, or the IGF1/IGFBP3 ratio (41%-155% higher risk). Conclusions: The 21-gene RS was related to favorable metabolic profiles including lower BMI, HOMA-IR, insulin, and C-peptide, and higher HDL in Chinese breast cancer patients, and its prognostic impact on breast cancer recurrence was more likely to present among patients with relatively favorable metabolic profiles.